Implementation of 16-QAM alamouti encoder on FPGA for MIMO testbed / Mohd Aminudin Mohd Khalid - Mohd Khalid, Mohd Aminudin (2014)
This project is aimed at implementing Alamouti's scheme on Polarizpne's FPGA-based software defined radio platform and also to conduct experiment with RF transmission. A 16-QAM encoder is implemented in this project successfully. The system manages to encode incoming data to Alamouti codes by performing baseband signal processing and schedule its timing according to Alamouti encoding scheme. Detail design specification is presented and future enhancement for decoding and channel estimation is proposed